A formação em Educação Física e as práticas de integralidade do cuidado na saúde coletiva - Silveira, Flávia Cristina dos Santos Matos (2012)
The formation in physical education comes accompanying and adapting itself to the market logic, forming professionals that attend to an intervention diversity, as in the school field as in the health field. The present work analyzed the formation contribution in physical education for professionals' performance regarding the care completeness practices in the Public Health, by means of the analysis of the curricular matrix and menus of a higher education institution, of the professionals' perception of the area and the new conformation of the current curricular matrix courses of physical education. It is a descriptive study, of qualitative nature, in which were analyzed the curricular matrix, the menus of one of the courses of physical education that have formed groups acting in the labor market and a data collection mixed instrument applied to professionals of physical education that work on the attention to the collective health, in the Psychosocial Attention Centers (CAPS), City Academy and in the Administration. The results evidence that professional's formation occurred in a technical-sports way, through a fragmented curricular structure, that valorized the disciplines of biological mark in disciplines detriment geared to the Human Sciences. The actions developed by the City Academy's professionals and former-professionals refer to the practice of physical activities with groups of senior, obese, hypertensive and diabetic, with difficulty, and even with, ignorance regarding to the articulation accomplishment in the actions network and planning. The professionals of CAPS accomplish corporeal practices and activities related to service working process close to users of mental, family, professional health and some accomplish planning and articulations in network. The Administration professionals related develop actions in the administration sphere in public policies, supervising, planning, institutional support, articulation, monitoring and services evaluation of mental health close to workmen of the area. It realizes that professionals' City Academy actions relate to the nuclear activities ruled in the specific formation obtained in physical education, with base in a technical and biomedical model for the practice of physical activities. It is observed that the corporeal practices, developed by the professionals of CAPS, adapt to the needs to users and to the working process and service care and, the actions accomplished in the administration sphere enlarge the knowledge field and professional intervention, however little use of the nuclear knowledge of the physical education. Thus, besides the dominant character of the biomedical model, so much in the formation as in the professionals'performance, the formation in physical education, with the curriculums development, contributes indirectly for the performance of the same in the Public Health.